Assessment of dietary intake of polychlorinated dibenzo-p-dioxins and dibenzofurans and dioxin-like polychlorinated biphenyls from the Chinese Total Diet Study in 2011. (October 2015) - Zhang, Lei; Yin, Shuaixing; Wang, Xiangyong; Li, Jingguang; Zhao, Yunfeng; Li, Xiaowei; Shen, Haitao; Wu, Yongning
Highlights: Dietary intake for adults was below the PTMI indicating low health risk in China. Large variations of dioxin level and dietary intake were found among regions. Increasing exposure was found in some regions partly due to rising contamination. Abstract: The concentrations of polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) as well as dioxin-like polychlorinated biphenyls (dl-PCBs) were measured in food samples from the fifth Chinese Total Diet Study (TDS) performed in 2011. A total of 152 composite samples from various food groups were analyzed by high resolution gas chromatography–high resolution mass spectrometer (HRGC–HRMS). The dietary intakes of PCDD/Fs and dl-PCBs were subsequently estimated for the adult from various regions in China. The mean dietary intake of PCDD/Fs and dl-PCBs was 20.1 pg TEQ kg −1  bw month −1 (WHO-TEF of 1998) within a range of 4.2 pg TEQ kg −1  bw month −1 to 53.7 pg TEQ kg −1  bw month −1 which were all much lower than the provisional tolerable monthly intake (PTMI) established by Joint FAO/WHO Expert Committee on Food Additives (JECFA). By comparing with results from previous Chinese TDS, a decline of the average dietary intake was observed from 2000 to 2011, but a notable elevation was observed in some regions partly stem from increasing contamination levels in certain foods.